Implementation of Drug Abuse Education Policy for Senior High School Students - Eka Kumala, Rendra; Amalia, Kaniati; Khamidi, Amrozi; Hazin, Muffarihul (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyze the implementation of the policy on drug abuse education programs for students in Senior High Schools. The main focus of this research is to examine the extent to which government and institutional policies have been effectively implemented within the school environment. The problem identified in the field indicates that the implementation of anti-drug education programs has not been optimal, due to limited coordination among stakeholders, inadequate resources, and the low level of teacher and student participation in preventive activities.This research employed a qualitative descriptive approach with a case study design conducted in several Senior High Schools that implemented drug abuse education programs. Data were collected through in-depth interviews, observations, and document analysis. The research questions focused on: (1) how the policy on drug abuse education programs is implemented in schools; (2) what factors support and hinder its implementation; and (3) how the implementation of the policy affects students’ understanding and attitudes toward drug abuse prevention.The results revealed that the policy implementation was partial and not yet fully integrated into the curriculum or school culture. The main supporting factors included the strong commitment of school principals and partnerships with the National Narcotics Board (BNN), while the main inhibiting factors were limited human resources, weak policy monitoring, and a lack of contextualized educational materials. Nevertheless, the program has had a positive impact on improving students’ awareness and preventive attitudes toward drug abuse, especially when activities were conducted collaboratively and sustainably.